Sweden : Financial Sector Assessment Program; Detailed Assessment of Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Detailed Assessment of Observance of Standards and Codes in Sweden. The assessment reveals that the laws and regulations on banking activities and their supervision are in place in Sweden. The composition of the Board of the Swedish Financial Supervisory Authority (FI) is not regulated in law or other ordinances. The position of the FI in relation to other public agencies in possible crisis situations is not defined in law. The FI has also made a motion to the government for a large increase in the number of specialists in its employ.